Borderline Personality Disorder: Emerging Symptoms, Evolving Therapies, and the Role of Physical Activity in Treatment - Sokół, Aleksandra; Majewska, Maria; Ignatiuk-Chilkiewicz, Marta; Kałuska, Joanna; Nowicka, Katarzyna; Mościszko, Klaudia; Klimek, Wiktor; Hakało, Dominika; Rafałowicz, Adam; Suprun, Tomasz (Quality in Sport, 2025)
Background: Borderline Personality Disorder (BPD) is a complex and heterogeneous mental health condition, traditionally characterized by emotional dysregulation, impulsivity, unstable interpersonal relationships, and a distorted self-image. In recent years, clinical research has increasingly identified atypical symptom presentations and highlighted challenges related to diagnosis, treatment responsiveness, role of physical activity and long-term prognosis. Aim: This review aims to provide a comprehensive overview of emerging symptoms associated with BPD, assess the development of novel and evolving therapeutic approaches, role of physical activity in treatment and discuss key prognostic factors that influence clinical outcomes. Material and Methods: A systematic literature review was conducted using PubMed as a primary database. Peer-reviewed articles published between 2000 and 2024 were included, with a focus on empirical studies, meta-analyses, and recent clinical guidelines related to BPD symptomatology, treatment, and prognosis. Conclusions: Understanding the broader spectrum of BPD symptoms and the dynamic nature of treatment response is essential for accurate diagnosis and effective intervention. An individualized, trauma-informed approach combined with ongoing research into prognostic markers holds promise for improving long-term outcomes in individuals with BPD.